The Islamic Education Perspective on Proactive Legal Protection and Hifz a-Mal: Highlighting the Rights of Domestic Workers in Medan - Suria Ningsih; Nurhayati Nurhayati; Dhiauddin Tanjung (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
At the very minimum, every worker's rights include a decent salary, reasonable working hours, and access to social security. All workers, including domestic workers, are included in the worker in consideration (PRT). In general, metropolitan regions, including Medan, are areas that within the